Implikasi Afwezigheid Serta Kedudukan Hukum Orang Tidak Hadir Di Dalam Perkawinan - Syarifah Amalia Bin Tahir; Robby Putri Aulia Franata; Mada Ali Haykal Sidiq (Fakultas Hukum Universitas Bangka Belitung, 2021)
A state of absence (Afwezigheid), which is a state where a person is not exist at the place of residence for a certain period of time. A person who is declared as afwezigheid results in his position according to the Civil Law being considered as juridical death, this causes their rights and obligations to be potentially deleted. In this modern world with rapidly developing technology make it easy for people to connect with each other, and barriers of communication are not a cause for concern anymore, but there are riot events such as natural disasters that cannot be avoided that can make a person being able to declared as afwezigheid. Afwezigheid has serious implications for the fulfilment of one's rights and obligations, for example in marriage. The marital status of the absent person (Afwezig) has the potential to end and result in the transfer of rights and obligations such as marital property, inheritance and alimony of children, because the person’s status is equivalent to death. Based on the Burgerlijk Wetboek, afwezigheid issues need to go through a process and require a court decision regarding the status or position of an afwezig on ​​a request by the interests. New problems will also arise when the afwezig return when their rights and obligations have been removed and are transferred. As well known, court decisions that have legal force can no longer be contested. Thus, the fate of those the absent person afwezig depends on the court's decision, because until now, there are no rules that explicitly regulate about the afweziheid.